A fuel-economy gauge for the rest of us. - Schneider, D.
The price of gasoline is down from its stratospheric highs of last July, but there are still plenty of reasons to conserve fuel and plenty of ways to do so. Drivers can make changes in their cars and better yet, in themselves; unfortunately, the human element isn't easy to tweak. That's partly because we lack detailed real-time data about which driving behaviors are wasteful.